1997
DOI: 10.33584/jnzg.1997.59.2245
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dairy pastures - the need for standardisation

Abstract: A study was undertaken to determine the reason for the differences in the estimation of pasture mass between dairying research centres in New Zealand and to define a common system of estimation that would overcome these differences and be able to describe the pasture situation on commercial dairy farms in different parts of New Zealand. Differences in the visual estimation of pasture between a standard observer and a local observer at the different dairying research centres in the order of 900 kg DM/ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…Cutting above ground level to leave a constant stubble height was found by Michell and Large (1983) to introduce a bias, because there were differences in herbage mass below the same stubble height, depending on season and sward height. It is recommended for New Zealand dairy pastures (Thomson et al ., 1997) to use ground level as a reference base because sampling height must be consistent.…”
Section: Discussionmentioning
confidence: 99%
“…Cutting above ground level to leave a constant stubble height was found by Michell and Large (1983) to introduce a bias, because there were differences in herbage mass below the same stubble height, depending on season and sward height. It is recommended for New Zealand dairy pastures (Thomson et al ., 1997) to use ground level as a reference base because sampling height must be consistent.…”
Section: Discussionmentioning
confidence: 99%
“…The partition of herbage mass between live and dead material, and the tiller population density (tillers m −2 ), were measured within circular quadrats with the same diameter (354 mm) as the platemeter when grazing‐behaviour measurements were made. The grass was cut to ground level (Frame, 1981; Thomson et al. , 1997) using scissors and subsamples of 50–60 grass tillers were separated into green leaves, green vegetative and reproductive stems, and dead material.…”
Section: Methodsmentioning
confidence: 99%
“…This ranged from 25-50 readings per paddock. Thomson et al (1997) indicated that 50-80 readings per paddock should be taken to obtain the most accurate estimate of average herbage mass. L'Huillier & Thomson (1988) mention that little difference was found between different users when correct procedures were followed.…”
Section: Average Herbage Massmentioning
confidence: 99%